2018
DOI: 10.1002/jcp.27042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carnitine palmitoyltransferases on cancer cellular senescence

Abstract: The carnitine palmitoyltransferase (CPT) family is essential for fatty acid oxidation. Recently, we found that CPT1C, one of the CPT1 isoforms, plays a vital role in cancer cellular senescence. However, it is unclear whether other isoforms (CPT1A, CPT1B, and CPT2) have the same effect on cellular senescence. This study illustrates the different effects of CPT knockdown on PANC-1 cell proliferation and senescence and MDA-MB-231 cell proliferation and senescence, as demonstrated by cell cycle kinetics, Bromodeox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…In previous sections, we mentioned the importance of oxidation of fatty acids and increased expression of CPTC1 in cancer cells. Recently, it has been shown that inhibition of CPTC1 causes increased senescence of cancer cells, and can be considered as a new therapy approach for treatment of cancer (Guan et al, 2019). Some studies have also focused on the metabolism of amino acids for treatment of cancer.…”
Section: Metabolism As Target For Cancer Treatmentmentioning
confidence: 99%
“…In previous sections, we mentioned the importance of oxidation of fatty acids and increased expression of CPTC1 in cancer cells. Recently, it has been shown that inhibition of CPTC1 causes increased senescence of cancer cells, and can be considered as a new therapy approach for treatment of cancer (Guan et al, 2019). Some studies have also focused on the metabolism of amino acids for treatment of cancer.…”
Section: Metabolism As Target For Cancer Treatmentmentioning
confidence: 99%
“…CPT1C, an enzyme located in the outer mitochondrial membrane [32], is involved in lipid metabolism, cellular energy supply [33][34][35] and other physiological or pathological processes [36][37][38][39]. The knockdown of CPT1C inhibited the tumorigenesis of PANC-1 cells in vivo [2,33] and further suppressed xenograft tumor growth in situ [2], suggesting that CPT1C represents a therapeutic target for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial respiration was evaluated by the OCR with a Seahorse XF-96 Extracellular Flux Analyzer (Seahorse Bioscience) as described previously (Guan et al, 2019;Wang et al, 2018). Briefly, 2 × 10 4 cells were seeded in XF-96 cell culture plates (Seahorse Bioscience) overnight and the medium was replaced with XF assay medium (Seahorse Bioscience) the next day.…”
Section: Oxygen Consumption Rate (Ocr) Analysis Using Seahorse Cellmentioning
confidence: 99%
“…It has been reported that CPT1C promotes tumor cell and stem cell survival under metabolic stress conditions (Roa‐Mansergas et al, 2018; Wang et al, 2017; Zaugg et al, 2011). Most recently, we found that CPT1C is a key regulator of tumor cell proliferation and senescence (Chen et al, 2017; Wang et al, 2018), exerting the most prominent role in mitochondrial dysfunction‐associated cellular senescence compared with other subtypes (Guan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%